Influence of birth weight and post partum age on lamb mortality in Ethiopian Horro sheep - Gojam, Y.; Gizaw, Solomon; Thwaites, C.J.; Awgichew, K. (Ethiopian Society of Animal Production, 1995)
Mortality was studied in relation to birth weight (BWT) and postpartum age in 3083 Horro lambs born over 15 years at Bako Research Center, IAR. Pre-weaning mortality rose with declining BWT (log y = 2.20- 0.35X; r = 0.9981), but the influence after weaning was less pronounced and linear (y = 23.78-1.93X; r = 0.5271). Overall, 1066 (34.6%) of the lambs died; 19.1% of lambs born died before weaning and 19.1 % of lambs weaned died before one year of age. Significantly more lambs died in the first week of life (231/2953 = 7.8%) than in any subsequent 7-day period (0.2-1.9%, P<0.001). But, although significant (P<0.01), a transient rise in mortality after weaning was small in magnitude (mean: 1.6 VS. 1.1% lambs died per week). Major gains in meat output could be achieved from Horro sheep by reducing lamb mortality; firstly by improved late-pregnancy health and nutrition of ewes, and thus BWT, and secondly by attention to ewe and lamb management during the first week after lambing.